1990
DOI: 10.1246/cl.1990.597
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Asymmetric Induction in the Reaction of Organometallics to β-Hydroxy Ketones and β-Silyloxy Ketones

Abstract: High level of 1,3-asymmetric induction was realized in the reaction between β-hydroxy ketones and triisopropoxytitanium reagents to give anti-1,3-diols possessing tertiary alcohols. To the contrary, syn-1,3-diols were obtained by the addition reaction of organometallics to β-t-butyldimethylsilyloxy ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[4] Fujisawa et al [5] reported that the treatment of b-hydroxy ketones, which have a stereocenter in the b-position, with MeTiCl 3 and MeTi(OiPr) 3 yielded mainly anti-diols, whereas reactions of the corresponding b-silyloxy ketones with lithium, magnesium, and titanium reagents afforded isomeric mixtures in which syn-diols were predominant. Anti-diols, as the prevalent diastereoisomers, were obtained by Ruano et al [6] in the methylation of b-hydroxy ketones with MeLi in the presence of ZnBr 2 , while formation of syn-diols was observed when Me 3 Al was used as the methylating agent.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Fujisawa et al [5] reported that the treatment of b-hydroxy ketones, which have a stereocenter in the b-position, with MeTiCl 3 and MeTi(OiPr) 3 yielded mainly anti-diols, whereas reactions of the corresponding b-silyloxy ketones with lithium, magnesium, and titanium reagents afforded isomeric mixtures in which syn-diols were predominant. Anti-diols, as the prevalent diastereoisomers, were obtained by Ruano et al [6] in the methylation of b-hydroxy ketones with MeLi in the presence of ZnBr 2 , while formation of syn-diols was observed when Me 3 Al was used as the methylating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, these mild conditions would also tolerate the presence of the nonanomeric AB spiroketal system in more advanced intermediates. Although hydroxyl-directed alkylations have rarely been used in total synthesis, the literature precedents were nevertheless encouraging …”
mentioning
confidence: 99%
“…The aldol union of ketone 5 and aldehyde 16 yielded the β-hydroxyketone 17 with excellent selectivity (Scheme ) and good yield. However, the key hydroxyl-directed methyltitanation of 17 required a considerable amount of experimentation to obtain a reproducible protocol. The reaction was much more sluggish than with the simpler C 10 −C 22 precursor aldol system .…”
mentioning
confidence: 99%